The exact synchronization timing between the cleavage embryo stage and duration of progesterone therapy-improved pregnancy rates in frozen embryo transfer cycles: A cross-sectional study - Marjan Omidi; Iman Halvaei; Fatemeh Akyash; Mohammad Ali Khalili; Azam Agha-Rahimi; Leila Heydari (Shahid Sadoughi University of Medical Sciences, 2021)
Background: Synchronization between the embryonic stage and the uterine endometrial lining is important in the outcomes of the vitrified-warmed embryo transfer (ET) cycles. Objective: The aim was to investigate the effect of the exact synchronization between the cleavage stage of embryos and the duration of progesterone administration on the improvement of clinical outcomes in frozen embryo transfer (FET) cycles. Materials and Methods: 312 FET cycles were categorized into two groups: (A) day-3 ET after three days of progesterone administration (n = 177) and (B) day-2 or -4 ET after three days of progesterone administration (n = 135). Group B was further divided into two subgroups: B1: day-2 ET cycles, that the stage of embryos were less than the administrated progesterone and B2: day-4 ET cycles, that the stage of embryos were more than the administrated progesterone. The clinical outcome measures were compared between the groups. Results: The pregnancy outcomes between groups A and B showed a significant differences in the chemical (40.1% vs 27.4%; p = 0.010) and clinical pregnancies (32.8% vs 22.2%; p = 0.040), respectively. The rate of miscarriage tended to be higher and live birth rate tended to be lower in group B than in group A. Also, significantly higher rates were noted in chemical pregnancy, clinical pregnancy, and live birth in group A when compared with subgroup B2. Conclusion: Higher rates of pregnancy and live birth were achieved in day-3 ET after three days of progesterone administration in FET cycles.